ANALISIS PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI MANFAAT, PERSEPSI RISIKO, DAN KEPUASAN KONSUMEN TERHADAP TRANSAKSI PEMBAYARAN SISTEMGO-PAY DAN CASH PADA GO-RIDE (STUDI PADA MAHASISWA UNIVERSITAS RIAU) - Juliyanti Syaripah; Restuti Sri; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Along with the development of the era, the needs of the community are increasing, one of which is the need for public transportation which is now a major need for the community. The competitiveness of the public transportation industry is growing with the existence of digital technology which is continuously being refined according to the needs of society. So that the creation of one of the online transportation, Go-ride by the Go-Jek company, which aims to make it easier for people to meet their needs for transportation, not only that, along with the development of the era, people also want convenience not only in the aspect of transportation but they also want convenience when transacting. , Go-Jek also offers convenience of transactions via electronic wallets, namely Go-pay, electronic wallets have been seen as a facility that provides convenience and benefits in transactions. However, many people view this technology as having risks, when it comes to payments. Even though it contains risks according to some people, many customers still trust and continue to use it, especially among students.Therefore, this study aims to determine how much the comparison of perceived ease of use, perceived usefulness, perceived risk and customer satisfaction of electronic wallets (Go-pay) and cash among students of the University of Riau in transactions when using Go-ride online transportation.The results of this study indicate that perceptions of ease of use, perceived usefulness, and perceived of risk towards the Go-pay system payment transactions are greater than cash payment transactions. Even though the risk perception of Gopay payment transactions is greater than cash payment transactions, the level of student satisfaction when using Go-pay payment transactions is greater than cash payment transactions.Keywords: Perceived of Ease of Use, Perceived Usefulness, Perceived of Risk, Consumer Satisfaction, Electronic Payment.